Pregnancy Outcome in Isolated Oligohydramnios at Term - Purvi K Patel; Dipa S Pitre; Harshita Gupta (Medsci Publications, 2015)
Introduction: The objective of this study was to compare the pregnancy outcome in cases with isolated oligohydramnios with low risk women having normal amniotic fluid volume. Methods: This prospective case control study included 80 women with isolated oligohydramnios (AFI < 5 but no maternal or fetal high risk factor) and these were compared with 320 low risk women with term pregnancy without oligohydramnios. Maternal and perinatal outcomes in pregnancies with oligohydramnios were compared with perinatal outcomes pregnancies with an amniotic fluid index > 5cm. Observations: The subjects with isolated oligohydramnios were associated with an increased incidence of Doppler abnormalities, CTG changes, meconium stained amniotic fluid and cesarean de- livery as compared to women with normal amount of amniotic fluid. There was no difference between the cases and controls as regards duration of labor, need for oxytocin augmentation, need for neonatal resuscitation, APGAR score at 5 minutes, NICU ad- mission, birth weight of neonates or incidence of LSCS for fetal distress. Conclusions: Apart from the increased cesarean section rate, which was partly attributable to the obstetrician's practice choic- es, there were no differences in the maternal or perinatal out- comes.